2019
DOI: 10.1111/cts.12710
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Regimens for Meropenem in Children with Pseudomonas Infections Do Not Meet Serum Concentration Targets

Abstract: There have been literature reports that some recommended meropenem dosage regimens may fail to meet therapeutic targets in some high‐risk children and adults. We evaluated this observation in children using literature studies conducted in infants and children. Observed and, as necessary, simulated data from the literature were combined, yielding a data set of 288 subjects (1 day to ~ 17 years). A population pharmacokinetic model was fit to the data and then used to simulate the recommended dosing regimens and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Then, we simulated the general optimal regimen and demonstrated that prolonging infusion to 4 h and 24 h with a lower dose (110 mg/kg/day) than those used previously by Cies et al (120 and 160 mg/kg/day as a continuous infusion against all susceptible Gramnegative bacteria [7]) would be efficacious and would reduce the overuse of meropenem. Hassan et al (15) illustrated that a 40 mg/kg/dose (q8h), 20 mg/kg/dose (q6h), or 20 mg/kg/dose (q8h) administered as a 3-h infusion should be efficacious. However, they did not enroll children with abnormal renal function or target critically ill children only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we simulated the general optimal regimen and demonstrated that prolonging infusion to 4 h and 24 h with a lower dose (110 mg/kg/day) than those used previously by Cies et al (120 and 160 mg/kg/day as a continuous infusion against all susceptible Gramnegative bacteria [7]) would be efficacious and would reduce the overuse of meropenem. Hassan et al (15) illustrated that a 40 mg/kg/dose (q8h), 20 mg/kg/dose (q6h), or 20 mg/kg/dose (q8h) administered as a 3-h infusion should be efficacious. However, they did not enroll children with abnormal renal function or target critically ill children only.…”
Section: Discussionmentioning
confidence: 99%
“…The standard dosing regimen for meropenem administered as 10 to 40 mg/kg of body weight/dose every 8 h (q8h) infused for 0.5 h has been shown to achieve the pharmacodynamic (PD) target of 40% fT ϾMIC in clinically stable children (13). However, it does not meet an appropriate PD target in critically ill children and should be optimized (7,14,15). Two studies have assessed the PK to explore the appropriate dose in critically ill children (7,14), but no covariates were identified due to the small number of children enrolled.…”
mentioning
confidence: 99%
“…At MICs of 2 and 4 mg/L, the PTAs were below 80%, the 3 h infusions increased PTAs to more than 99% at these MICs, and the PTAs could still reach 82.8% at 8 mg/L with good tolerability. In addition, Hassan et al [ 19 ] built PPK models using data pooled from published studies. The researchers also found that MICs of 2 and 4 mg/L and an EI time of 3 h yielded higher PTAs than conventional 0.5 h infusions did.…”
Section: Resultsmentioning
confidence: 99%
“…The Grading of Recommendations Assessment, Development and Evaluation approach (GRADE) was not performed, owing to the insufficient data. [19] PPK modeling and simulation children with infections 288/NA MER 10-40 mg/kg/dose q8 h-q12 h 1000 MER < 50 kg: 20 mg/kg/dose q8 h 0.5 h; 40 mg/kg/dose q8 h 0.5 h; 20 mg/kg/dose q6 h 0.5 h; 20 mg/kg/dose q8 h 3 h EI > 50 kg: 1 g/dose q8 h 0.5 h; 2 g/dose q8 h 0.5 h; 1 g/dose q6 h 0.5 h; 1 g/dose q8 h 3 h EI…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Meropenem shows time-dependent antibacterial activity related to the time that the plasma free concentration of meropenem exceeds the minimum inhibitory concentration (MIC) of the pathogen ( fT >MIC ) ( Mathew et al, 2016 ). Despite its wide use, the standard dosing regimen, administered as 10–40 mg/kg/dose (q8h) infused for 0.5 h, for critically ill infants, children ( Kongthavonsakul et al, 2016 ; Cies et al, 2017 ; Hassan et al, 2019 ; Wang et al, 2020 ) and adults( Alsultan et al, 2021 ) may fail to meet pharmacodynamic (PD) targets.…”
Section: Introductionmentioning
confidence: 99%